DEPRECIATION AND USER COST. - Ross, Myron H. (The Accounting Review, 1960)
The above theoretical considerations suggest that some revision in present depreciation practices may be appropriate. Wider application of depreciation based on output would approach measuring user cost more closely than the present methods in use. Most methods implicitly assume the absence of the business cycle or economic growth. Canadian-Pacific Railways, in basing depreciation on use, recognizes the importance of economic change. Since user cost is closely linked with changing economic conditions, perhaps more frequent revisions of depreciation schedules are called for. The California Public Utility Commission suggests that annual revisions be made. When technological innovation is accelerated, the life of assets is shortened by increased obsolescence. User cost is as variable as the underlying economic conditions which influence the value of fixed assets. Break-even analysis is generally not dear concerning the nature of depreciation. Depreciation is usually considered a fixed cost. Yet consideration must be given to the fact that present use affects the future value of fixed assets, as well as income. Thus in trying to determine the cost of an additional work shift, for example, one must include the additional wear and tear on plant and machinery. Often because this is not done, the additional shift appears profitable, but is in fact unprofitable. Accounting information should attempt to estimate user cost in order to avoid such errors. Businessmen are not indifferent to the erosion of assets resulting from changes in production and there is little reason why accountants should be. While straight-line computations of depreciation are precise, they are often irrelevant for making business decisions. An approximation of user cost would be preferable. It is true that "user cost is a concept widely known, little understood and almost never used." This should be rectified.